2008
DOI: 10.1088/0953-8984/21/2/023203
|View full text |Cite
|
Sign up to set email alerts
|

Wigner crystal physics in quantum wires

Abstract: Abstract. The physics of interacting quantum wires has attracted a lot of attention recently. When the density of electrons in the wire is very low, the strong repulsion between electrons leads to the formation of a Wigner crystal. We review the rich spin and orbital properties of the Wigner crystal, both in the one-dimensional and quasi-one-dimensional regime. In the one-dimensional Wigner crystal the electron spins form an antiferromagnetic Heisenberg chain with exponentially small exchange coupling. In the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
168
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(177 citation statements)
references
References 81 publications
(269 reference statements)
7
168
1
1
Order By: Relevance
“…While the NC wave function remains essentially unaltered by the dielectric confinement, the NR wave function develops a valley in the center of the structure. This is a clear indication that Wigner localization is taking place in the NR, which will have direct implications for transport processes 26 and shell-filling spectroscopy.…”
Section: Electron-electron Interactionmentioning
confidence: 85%
“…While the NC wave function remains essentially unaltered by the dielectric confinement, the NR wave function develops a valley in the center of the structure. This is a clear indication that Wigner localization is taking place in the NR, which will have direct implications for transport processes 26 and shell-filling spectroscopy.…”
Section: Electron-electron Interactionmentioning
confidence: 85%
“…Upon increasing density (and, thus, the interaction energy), or weakening the confining potential, the crystal deviates from its strictly one-dimensional structure. It has been shown that at a critical density, a transition to a zigzag crystal takes place 7,11,23,25,26 . Though not for electrons, this zigzag transition has indeed been observed using 24 Mg + ions in a quadrupole storage ring 27 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, when d = 1 the system serves as a prototype for ions in electromagnetic traps and when d = 3, as a model of confined dipolar particles. Here we address mainly the limit as g → ∞ in which the perfect linear Wigner molecule is formed [35][36][37], and the harmonic approximation (HA) is valid [11,14,38,39]. Recently, within the framework of this approximation, we have derived when N = 3 and d = 1 an explicit integral representation for the asymptotic occupancies and their natural orbitals [11].…”
Section: Introductionmentioning
confidence: 99%